2015
DOI: 10.1007/s13277-015-3711-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from women with breast cancer promote an epithelial-mesenchymal transition-like process in mammary epithelial cells MCF10A

Abstract: Extracellular vesicles (EVs) mediate many stages of tumor progression including angiogenesis, escape from immune surveillance, and extracellular matrix degradation. We studied whether EVs from plasma of women with breast cancer are able to induce an epithelial-mesenchymal transition (EMT) process in mammary epithelial cells MCF10A. Our findings demonstrate that EVs from plasma of breast cancer patients induce a downregulation of E-cadherin expression and an increase of vimentin and N-cadherin expression. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Overexpression of N-cadherin in primary melanomas and the loss of E-cadherin expression in primary melanomas and metastatic melanomas correlated with worse overall survival of CM patients [18]. The absence of E-cadherin and the presence of N-cadherin in CM ectosomes may reflect their potential to induce or promote EMT in recipient cells and such properties have already been shown for exosomes released by bladder cancer cells [19] and exosomes from plasma of breast cancer patients [20]. Additionally, Qendro et al [4] demonstrated that the pattern of vimentin expression in exosomes can help predict tumor aggressiveness in different subtypes of melanoma.…”
Section: Proteins Involved In Cancer Progression Detected In Cm-derivmentioning
confidence: 67%
“…Overexpression of N-cadherin in primary melanomas and the loss of E-cadherin expression in primary melanomas and metastatic melanomas correlated with worse overall survival of CM patients [18]. The absence of E-cadherin and the presence of N-cadherin in CM ectosomes may reflect their potential to induce or promote EMT in recipient cells and such properties have already been shown for exosomes released by bladder cancer cells [19] and exosomes from plasma of breast cancer patients [20]. Additionally, Qendro et al [4] demonstrated that the pattern of vimentin expression in exosomes can help predict tumor aggressiveness in different subtypes of melanoma.…”
Section: Proteins Involved In Cancer Progression Detected In Cm-derivmentioning
confidence: 67%
“…O'Brien et al demonstrated that exosomes isolated from an invasive variant of triple negative breast cancer (TNBC) cells (Hs578Ts (i)8 ) caused an increase in the growth rate, migration, and invasive capacity of SKBR3, MDA-MB-231, and HCC1954 breast cancer cell lines, as well as causing an increase in endothelial cell angiogenesis [ 50 ]. Galindo-Hernandez et al reported that an epithelial-mesenchymal transition-like process was induced in MCF10A cells by EVs isolated from plasma of women with breast carcinoma [ 151 ]. Exosomes from the serum of patients with TNBC also produced significantly greater invasion of breast cancer cell lines compared to exosomes from healthy donors [ 50 ].…”
Section: Ev Contribution To Breast Tumor Growth and Metastasismentioning
confidence: 99%
“…As a result, intercellular contacts and apical-basal polarity are lost, and tumor cell motility is enhanced via reorganization of the actin cytoskeleton and the intermediate filament network (Thiery et al, 2009;May et al, 2011). EMT-associated transcription factors can also stimulate secretion of gelatinases and matrix metalloproteinases (MMPs), leading to remodeling of the extracellular matrix (ECM) (Galindo-Hernandez et al, 2015;Shen et al, 2017). The induction of EMT in carcinomas can further increase tumor angiogenesis via enriching CSCs which possess the capacity to differentiate into endothelial cells and also upregulate the expression of the pro-angiogenic transcription factor VEGF-A (Fantozzi et al, 2014;Delgado-Bellido et al, 2017).…”
Section: Escape From the Primary Tumor Site And Intravasation Into Thmentioning
confidence: 99%